2015
DOI: 10.1007/s11912-015-0449-x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound in Gynecological Cancer: Is It Time for Re-evaluation of Its Uses?

Abstract: Ultrasound is the primary imaging modality in gynecological oncology. Over the last decade, there has been a massive technology development which led to a dramatic improvement in the quality ultrasound imaging. If performed by an experienced sonographer, ultrasound has an invaluable role in the primary diagnosis of gynecological cancer, in the assessment of tumor extent in the pelvis and abdominal cavity, in the evaluation of the treatment response, and in follow-up. Ultrasound is also a valuable procedure for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 53 publications
(69 reference statements)
2
35
0
Order By: Relevance
“…Moreover, our results are also comparable with those of a recently published study by Michielsen et al . comparing whole‐body MRI with DWI (WB‐DWI/MRI) for ovarian cancer staging with CT and F‐fluorodeoxyglucose (FDG)‐PET/CT; in the assessment of pelvic carcinomatosis, WB‐DWI/MRI had a sensitivity of 92% ( vs our 81%) and specificity of 95% ( vs our 97%), while CT and PET/CT achieved a significantly lower sensitivity (sensitivity, 56% and 36%; specificity, 95% and 100%, respectively).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, our results are also comparable with those of a recently published study by Michielsen et al . comparing whole‐body MRI with DWI (WB‐DWI/MRI) for ovarian cancer staging with CT and F‐fluorodeoxyglucose (FDG)‐PET/CT; in the assessment of pelvic carcinomatosis, WB‐DWI/MRI had a sensitivity of 92% ( vs our 81%) and specificity of 95% ( vs our 97%), while CT and PET/CT achieved a significantly lower sensitivity (sensitivity, 56% and 36%; specificity, 95% and 100%, respectively).…”
Section: Discussionsupporting
confidence: 90%
“…For CT we also found similar results to those reported in previous studies23–25 (see online supplementary table S2). Interestingly, ultrasound—specifically transvaginal ultrasound—showed a rather better diagnostic performance than CT for the assessment of pelvic structures such as the recto-sigmoid and pelvic peritoneum, which is in agreement with findings reported by Fischerova and Cibula 26. In fact, these authors found that ultrasound might be as accurate as magnetic resonance imaging for assessing the pelvis in gynecological cancer.…”
Section: Discussionsupporting
confidence: 88%
“…if metal parts are present in the body; in the presence of a pacemaker; or cochlear implants. 17,19 With improvements in the resolution achieved by ultrasonic instruments and the accumulated experience of doctors, US can be used to observe whether the cervical line is interrupted or the cervical intima is thickened. Moreover, US is an economical and non-invasive technique that patients willingly accept, which has resulted in US becoming the preferred method for early diagnosis of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an increase of HPV-induced cancers and speci c concerns regarding post-vaccination infertility or pregnancy or infant outcomes were also raised. 16 Ultrasonography (US) is economical, convenient, non-invasive, and has been reported to have a diagnostic accuracy similar to that of magnetic resonance imaging (MRI) on local extension of the disease although it is not included in the protocols for cervical cancer, 17,18 so it is suitable for women with rare cervical cancers; speci cally, color Doppler US (CDUS) can enhance the display rate of malignant tumors by Doppler ow imaging, and achieve clear images of lesions for accurate staging and targeted cervical biopsy. Thus, the diagnostic sensitivity and positive predictive value can be improved, thereby providing a basis for selecting appropriate treatment methods.…”
Section: Introductionmentioning
confidence: 99%